Physiological changes associated with the diadromous migration of salmonids - Hogasen, Helga Rachel (Canadian special publication of fisheries and aquatic sciences, 1998)
The book reviews and discusses present knowledge concerning the diadromous migration of salmonids. It groups elements ranging from ecology to cell biology, to give the reader a background knowledge for critical understanding of published literature and for proper design of experiments.